Chronic illnesses and injuries: an evaluation of their impact on occupation and revenues. Maladies chroniques et accidents : une évaluation de leur impact sur le parcours professionnel et les revenus - Duguet, Emmanuel; Le Clainche, Christine (Noisy-le-Grand, 2012)
"This paper investigates whether chronic illnesses and injuries have a significant impact on the individual’s performance in the labor market. We use the “Santé et Itinéraires Professionnels” (SIP, “Health and Labor Market Histories”) survey, conducted in France in 2006-2007. We use the propensity score method in order to evaluate the impact of chronic illnesses and accidents on labor market participation and earnings. We find that both health events, chronic illness and accidents have a negative effect on professional careers and earnings, and that accidents have a greater impact on women’s earnings."